Monitoring growth of Uttis (Alnus nepalensis) at a plantation cite at Dhankuta, Nepal - Barakoti, T. P. (Banko Janakari, 2007)
A long-term growth monitoring experiment on Uttis (Alnus nepalensis) was conducted in the permanent sample plots of the Agricultural Research Station (ARS) Pakhribas, Dhankuta for 10 years (1992-2001). The average annual increment was diameter at breast height 2.14 cm in 8th year, and was 0.13 cm at 16th year of planting. The trees grew 44 cm to 130 cm per year irrespective of the age. The highest growth rate correspondend with higher rainfall during summer (March-April). Estimated biomass of stem and branches increased by 2-2.5 times within the 10 years period. Thinning and felling every year indicated need for timely management of the plantation to provide better growing environment. The data would be useful for growth modelling and proper management of Uttis plantation in Nepal . Key words: Nepalese alder vs Uttis, height, diameter, biomass, Pakhribas.Banko Janakari Vol.15(2) 2005 pp19-23